2022
DOI: 10.3389/fimmu.2022.975027
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition receptor CD14 gene polymorphisms in alcohol use disorder patients and its Influence on liver disease susceptibility

Abstract: BackgroundAlcohol use disorders (AUDs) leading to liver disease is major concern over other spectrum of disorder. Excessive alcohol consumption resulting in leaky gut syndrome is attributed to alcohol-induced liver injury through portal translocation of bacterial endotoxin. Susceptibility to alcoholic liver disease (ALD) in AUD patients could be dependent upon genes responsible for inflammation and alcohol metabolism. The pattern recognition receptor CD14 gene is a major player in endotoxin-mediated inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…Some biomarker changes may be associated with comorbid diseases. The findings of this study on the association of FABP2 and LBP with ALD (Figure 2) are supported by existing data [22,74]. The findings of increased zonulin in patients with concomitant pancreatitis are also consistent with the literature [75].…”
Section: Associations With Comorbid Pathologies and Clinical Variablessupporting
confidence: 91%
“…Some biomarker changes may be associated with comorbid diseases. The findings of this study on the association of FABP2 and LBP with ALD (Figure 2) are supported by existing data [22,74]. The findings of increased zonulin in patients with concomitant pancreatitis are also consistent with the literature [75].…”
Section: Associations With Comorbid Pathologies and Clinical Variablessupporting
confidence: 91%
“…[ 49 ] Another recent study from North India included 128 AUD patients with ALD, 184 AUD patients without ALD, and 152 controls without AUD. [ 50 ] As per the study findings, enhanced CD14 expression increases vulnerability to developing ALD among AUD patients with TT genotype.…”
Section: Factors Associated With Alcohol Usesupporting
confidence: 72%
“…Based on a large genome-wide association study, PNPLA3, transmembrane 6 superfamily member 2 (TM6SF2), and membrane-bound O-acyltransferase domain-containing protein 7 (MBOAT7) were determined to be associated with ALD progression presumably via modulating lipid metabolism and/or HCC risk, for which the exact mechanisms have remained unclear [ 57 ]. Further studies have identified an association between susceptibility to ALD and polymorphisms in the pattern recognition receptor CD14 gene, as well as in the nuclear factor erythroid 2-related factor 2 gene, both of which are involved in endotoxin-mediated inflammation and susceptibility to ALD [ 58 , 59 ]. Larger studies are needed to confirm these findings.…”
Section: Pathogenesismentioning
confidence: 99%